The migrant network effect : an empirical analysis of rural-to-urban migration in South Africa - Stapleton, Caroline (School of Economics, 2015)
Recent empirical migration literature in South Africa suggests that access to physical and human capital, in the way of finance and education respectively, are key factors in increasing one’s probability of migrating. This paper attempts to extend this literature by directly measuring the extent to which social capital, broadly defined as one’s access to a migrant network, affects the probability of rural-to-urban migration. Using the first nationally representative panel dataset in South Africa, the National Income Dynamics Study, and defining a rural-to-urban migrant as an individual who is observed moving from a rural area in the baseline wave (2008) to an urban area by Wave 3 (2012), I estimate a standard model of migration choice with the inclusion of one’s connection to a migrant network. This connection is measured by being part of a household in the baseline wave that contains somebody with current or recent experience as a labour migrant. In line with international migration literature, the empirical results suggest that access to a migrant network increases the likelihood of becoming a migrant (by between 2-3 percentage points). These findings are robust to the inclusion of the individual’s prior migration experience and employment status. Furthermore, an extension of the core analysis to assess the impact of genetic relatedness in conjunction with the migrant network effect suggests some evidence of a household bargaining process at play. The findings in this paper therefore suggest that social capital does indeed play a role along with physical and human capital in determining who migrates in South Africa.